Pengaruh Carbon Emission Disclosure dan Green Expenditure Terhadap Kualitas Laporan Keberlanjutan (Studi pada Perusahaan yang Tercatat di Indeks ESG Leaders pada Periode 2022-2024) - Muhammad Panggih Saputra; Insyirah Putikadea (Indo-MathEdu Intellectuals Journal, 2026)
This study aims to analyze the effect of carbon emission disclosure and green expenditure on the quality of sustainability reports in companies listed in the ESG Leaders Index for the 2022–2024 period. The study employed a quantitative approach with secondary data obtained from annual reports and corporate sustainability reports. Purposive sampling was used to select 19 companies with a total of 57 observational data sets over the three years of the study. Data collection was conducted through a documentary study of officially published corporate reports. Data analysis used multiple linear regression with the aid of statistical software. Prior to hypothesis testing, the data were subjected to classical assumption tests, including normality, multicollinearity, heteroscedasticity, and autocorrelation. The results showed that carbon emission disclosure had a positive and significant effect on the quality of sustainability reports. Meanwhile, green expenditure had no significant effect. However, both variables simultaneously had a significant effect on the quality of corporate sustainability reports.